Crystal structure of Mycobacterium tuberculosis O6-methylguanine-DNA methyltransferase protein clusters assembled on to damaged DNA - Miggiano, Riccardo; Perugino, Giuseppe; Ciaramella, Maria; Serpe, Mario; Rejman, Dominik; Páv, Ondřej; Pohl, Radek; Garavaglia, Silvia; Lahiri, Samarpita; Rizzi, Menico; Rossi, Franca (The Biochemical journal, 2016)
Mycobacterium tuberculosis O(6)-methylguanine-DNA methyltransferase (MtOGT) contributes to protect the bacterial GC-rich genome against the pro-mutagenic potential of O(6)-methylated guanine in DNA. Several strains of M. tuberculosis found worldwide encode a point-mutated O(6)-methylguanine-DNA methyltransferase (OGT) variant (MtOGT-R37L), which displays an arginine-to-leucine substitution at position 37 of the poorly functionally characterized N-terminal domain of the protein. Although the impact of this mutation on the MtOGT activity has not yet been proved in vivo, we previously demonstrated that a recombinant MtOGT-R37L variant performs a suboptimal alkylated-DNA repair in vitro, suggesting a direct role for the Arg(37)-bearing region in catalysis. The crystal structure of MtOGT complexed with modified DNA solved in the present study reveals details of the protein-protein and protein-DNA interactions occurring during alkylated-DNA binding, and the protein capability also to host unmodified bases inside the active site, in a fully extrahelical conformation. Our data provide the first experimental picture at the atomic level of a possible mode of assembling three adjacent MtOGT monomers on the same monoalkylated dsDNA molecule, and disclose the conformational flexibility of discrete regions of MtOGT, including the Arg(37)-bearing random coil. This peculiar structural plasticity of MtOGT could be instrumental to proper protein clustering at damaged DNA sites, as well as to protein-DNA complexes disassembling on repair.
Keywords: Crystallography; co-operativity; Protein Structure, Secondary; DNA repair; O(6)-methylguanin-DNA-methyltransferasa; sekundární struktura proteinů; krystalografie; bakteriální proteiny; bodová mutace; DNA-binding protein; Mycobacterium tuberculosis; Point Mutation; Bacterial Proteins; poškození DNA; DNA Damage; O(6)-Methylguanine-DNA Methyltransferase; O6-methylguanine-DNA methyltransferase; terciární struktura proteinů; crystal structure; Protein Structure, Tertiary